Global and local asymptotic stability of an epidemic reaction‐diffusion model with a nonlinear incidence. (8th March 2022) - Djebara, Lamia; Douaifia, Redouane; Abdelmalek, Salem; Bendoukha, Samir
Abstract : The aim of this paper is to study the dynamics of a reaction‐diffusion SI (susceptible‐infectious) epidemic model with a nonlinear incidence rate describing the transmission of a communicable disease between individuals. We prove that the proposed model has two steady states under one condition. By analyzing the eigenvalues and using the linearization method and an appropriately constructed Lyapunov functional, we establish the local and global asymptotic stability of the non‐negative constant steady states subject to the basic reproduction number being greater than unity and of the disease‐free equilibrium subject to the basic reproduction number being smaller than or equal to unity in ODE case. By applying an appropriately constructed Lyapunov functional, we identify the condition of the global stability in the PDE case. Finally, we present some numerical examples illustrating and confirming the analytical results obtained throughout the paper.